Efficacy of poultry manure and biochar of cassava peels on root-gall nematode (Meloidogyne incognita) of okra (Abelmoschus esculentus) in an endemic Ultisol.: Application of Biochar and Poultry Manure in Nematode-Infested Soils - COOKEY, CHINAEKWU; Keyagha, Rosemary; Umeh, Ogechukwu; Okoli, Nneka; Ogwudire, Vincent; Alagba, Rosemond; Echereobia, Christopher; Nwokeji, Ephraim (International Journal of Agricultural Technology, 2025)
In an endemic ultisol, the efficacy of poultry manure and biochar derived from cassava peels against the root-gall nematode of okra was investigated at Undergraduate Demonstrative Farms, Federal University of Technology, Owerri, Imo State, Nigeria. With four replicates, the field trial was a 2x4 factorial in a randomized complete block design. Two types of okra, Maha and Dizengoff okra, were used in the treatments, along with three organic soil amendments: poultry manure, biochar made from cassava peels, biochar made from cassava peels with poultry, and the control. The number of leaves, height of plant (cm), total number of pods, weight of pod (g), weight of shoot (g), weight of root (g), and root index (0–4) were the data that were taken. The Dizengoff okra variety yielded significantly (P<0.05) higher plant height (10.01 cm) and shoot weight (5.40 g) than Maha okra variety (8.44 cm and 5.19 g), respectively. The findings additionally demonstrated that the Maha okra variety exhibited higher quality in terms of pod weight (85.60 g) and number of pods (16.50 g), which varied considerably (P<0.05) from the Dizengoff okra variety’s 12.06 and 75.00 g, respectively. Compared to all other soil amendments employed in this study, okra plant growth and yield parameters were boosted in plots treated with a mixture of biochar made from cassava peels and poultry manure. The best way to lessen the harm that the nematode did to the okra plant was to apply a mixture of biochar made from cassava peels and poultry manure. This mixture can be utilized as a sustainable management technique against the root-gall nematode (Meloidogyne incognita) in an endemic soil.